Empowering the Young Generation Through Entrepreneurship in Bone Regency (Weaving Hope, Seizing Opportunities) - A. Rahmatia; Rosnaeni Arsyad; Muh Ridwan (ITEKES Permata Ilmu Maros, 2025)
Bone Regency, is an area rich in traditional values ​​and abundant natural resource potential. However, its young generation still faces serious challenges: unemployment, urbanization, and limited access to entrepreneurship training. This community service activity aims to develop the potential of the young generation through an entrepreneurship-based empowerment approach. This approach is not only an economic strategy, but also a way to build independence, creativity, and social sustainability.